Metabolically speaking Possible reasons behind the tolerance of 'Sugar Belle' mandarin hybrid to huanglongbing - Killiny, Nabil (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2017 Elsevier Masson SAS. All rights reserved.